Laughing at Unbearable Urges: Reshaping the Male-Authored Script of Desire - Polachek, Dora E. (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2015)
As Pierre Champion noted a half a century ago, “The Cent Nouvelles nouvelles open a secret door into the house of men of that time.” The misogynous aspect of these novellas, designed to inspire laughter, is evident in most of the stories dealing with masculine drives and uncontrollable desires of husbands to seduce other women without being discovered. Novella 9 is a prime example of such a scenario, a novella that serves as Marguerite de Navarre’s intertext in the Heptaméron’s novella 8. In this article I will analyze how Marguerite reshapes her fifteenth-century intertext in order to promote a highly protofeminist agenda. All the while maintaining the same structure and characters, she introduces changes that are both subtle and radical. The focus of my analysis will show how these changes put into question the masculinist vision offered by CNN 9 and open instead a space for a commentary on women’s agency and their quest for their own pleasure.